Marriage Identity Forgery in Indonesia: Legal Consequences and Systemic Loopholes Perspective - Tumiwa, Anisa Jihan; Taufik, Muhammad; Sidqi, Imaro (ANTMIND YOUTH EMPOWER FOUNDATION, 2025)
This study explores the phenomenon of identity forgery in marriage registration in Indonesia, an issue that undermines the legitimacy of marital unions and creates complex legal, social, and administrative consequences. Using a normative juridical approach, this research examines statutory regulations, court decisions, and official reports to identify the primary forms of identity forgery, ranging from falsifying personal identification documents to manipulating marital and religious status. The analysis reveals that the absence of an integrated, real-time population database, heavy reliance on physical documents, insufficient verification mechanisms, limited staff training, and low legal literacy are key systemic weaknesses that enable identity forgery to persist. Under Indonesian law, marriages based on forged identities are subject to annulment, which may lead to disputes over property, inheritance, and child custody. Although the law protects the rights of children born from annulled marriages, the administrative and legal complexities remain significant. The study concludes by recommending the urgent development of an integrated digital identity verification system, continuous training for registration officers, strengthened internal and external oversight, and enhanced public legal education. These measures are necessary to safeguard the integrity of marriage law in Indonesia and prevent further abuse of the system.